2016
DOI: 10.1093/hmg/ddw374
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of cGMP signalling in photoreceptors by a macular dystrophy-related mutation in the calcium sensor GCAP1

Abstract: Macular dystrophy leads to progressive loss of central vision and shows symptoms similar to age-related macular degeneration. Genetic screening of patients diagnosed with macular dystrophy disclosed a novel mutation in the GUCA1A gene, namely a c.526C > T substitution leading to the amino acid substitution p.L176F in the guanylate cyclase-activating protein 1 (GCAP1). The same variant was found in three families showing an autosomal dominant mode of inheritance. For a full functional characterization of the L1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Leu 176 replacement by Phe, through the altered tug action, increases GCAP1 affinity for RetGC1 but also reduces the affinity of the EF-hand 4 for Ca 2ϩ and thus shifts Ca 2ϩ sensitivity of RetGC regulation outside the physiological range (43). The L176F substitution, originally used to change the calcium-myristoyl tug in GCAP1 in vitro (43), was soon after found in patients with a photoreceptor dystrophy (44), likely triggered by elevated cGMP production in the dark.…”
Section: Molecular Mechanisms Of Retinopathies Caused By Gcap Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leu 176 replacement by Phe, through the altered tug action, increases GCAP1 affinity for RetGC1 but also reduces the affinity of the EF-hand 4 for Ca 2ϩ and thus shifts Ca 2ϩ sensitivity of RetGC regulation outside the physiological range (43). The L176F substitution, originally used to change the calcium-myristoyl tug in GCAP1 in vitro (43), was soon after found in patients with a photoreceptor dystrophy (44), likely triggered by elevated cGMP production in the dark.…”
Section: Molecular Mechanisms Of Retinopathies Caused By Gcap Mutationsmentioning
confidence: 99%
“…nant cone or cone-rod degenerations specifically suppress Ca 2ϩ sensitivity of RetGC1 isozyme in vivo (17,41,42), most often by directly altering GCAP1 EF-hand motifs and thus reducing metal binding in EF-hands 3 and 4 (reviewed in Ref. 21), but also indirectly, by affecting EF-hand 4 affinity for Ca 2ϩ via altering a "calcium-myristoyl tug" mechanism connecting the C-terminal EF-hand 4 with the N-terminal myristoyl group buried inside the N-proximal semiglobule of EF-hands 1 and 2 (1,43,44). Here we describe a new type of mutation in GCAP1, G86R, leading to a dominant retinopathy in humans.…”
mentioning
confidence: 99%
“…Synthesis of cyclic GMP (cGMP) is an essential process in photoreceptor cells of the retina, as cGMP is the signaltransducing molecule in the light response 1,2 . Mutations in a number of genes that impair or alter cGMP synthesis in rods and cones have been associated to different forms of blindness [3][4][5][6][7][8][9][10][11][12] . Loss-of-function mutations in the RD3 gene (name from the natural strain of "retinal degeneration 3" mice, rd3 locus mutated) cause Leber's congenital amaurosis 12 (LCA12) 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in GUCA1A, encoding for GCAP1 result in aberrant GC regulation and in retinal degeneration, a set of progressive diseases involving cones, the macula, and in some cases rods, ultimately leading to blindness [11][12][13]. To date, 20 GCAP1 variants have been associated with retinal dystrophy [14][15][16][17][18][19][20][21][22][23][24][25], with one of the most recently discovered being the G86R mutation, located in the previously mentioned hinge region [26]. Biochemical experiments performed with the GC-GCAP1 reconstituted system in the presence of the G86R mutation showed that the complex forms with higher affinity than the WT and it is unable to decelerate the GC at high Ca 2+ -levels corresponding to the dark-adapted state [26].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed biochemical and biophysical studies reported a similar common molecular mechanism of dysregulation among the majority of GCAP1 variants [20,[27][28][29][30][31][32], namely, a reduced Ca 2+ -affinity due to mutations in EF3 and EF4. On the other hand, some disease-associated mutations resulted in an unaltered Ca 2+ -sensitivity [24,33], suggesting that GC dysregulation may arise from higher affinity for Mg 2+ or from alterations in the long-range allosteric communication between the EF-hands and the target interface [10].…”
Section: Introductionmentioning
confidence: 99%